ABREVIASI DALAM PERCAKAPAN SEHARI-HARI DI MEDIA SOSIAL: SUATU KAJIAN MORFOLOGI (ABBREVIATION IN EVERYDAY CONVERSATION ON SOCIAL MEDIA: A MORPHOLOGICAL STUDY) - Rengganis Citra Cenderamata; Agus Nero Sofyan (Prasasti: Journal of Linguistics, 2019)
This research is entitled “Abbreviation in Everyday Converstion on Social Media: A Morphological Study”. The method used in this study is a qualitative method. The data are taken from everyday conversation on social media such as line, whatsapp, facebook, twitter, and instagram. The theory are used abbreviation process and slang language. The aims of this study are to describe the common features of abbreviation process used by young and adult Indonesian people. Based on the research, it is indicated that the participants used three most common abbreviation processes are acronym, blending, and clipping in everyday conversation on social media. Acronym and blending found as the most common abbreviation process among the three features. As for the reasons of this language phenomenon occurrence identified are the participants intend to save time, fill the communication gap or barrier among the users, and indicate the social group.